Against Health : How Health Became the New Morality. - Metzl, Jonathan M. (Biopolitics: Medicine, Technoscience, and Health in the Twenty-first Century., 2010)
You see someone smoking a cigarette and say, "Smoking is bad for your health," when what you mean is, "You are a bad person because you smoke." You encounter someone whose body size you deem excessive, and say, "Obesity is bad for your health," when what you mean is, "You are lazy, unsightly, or weak of will." You see a woman bottle-feeding an infant and say, "Breastfeeding is better for that child's health," when what you mean is that the woman must be a bad parent. You see the smokers, the overeaters, the bottle-feeders, and affirm your own health in the process. In these and countless other i.